Utilization of Renewable Emission Neutral Garbage Solution Equipment (RENGSE) as Waste Management Technology in Mekar Jaya Village - Latuconsina, Hudaya; Sofia Latif, Inas (Universitas Ahmad Dahlan, 2025)
Background: This article presents the application of environmentally friendly renewable waste technology called RENGSE in Mekar Jaya Village, Tangerang Regency as part of a technology-based community service program. Contribution: The initiative to create and operate RENGSE for the management of various types of waste (organic and non-organic) based on thermal combustion that is specifically designed so as not to produce harmful emissions. Method: The methodology used is Participatory Action Research (PAR) with stages including counseling, technology operation training, mentoring and direct practice, as well as monitoring and evaluation. Results: The results obtained from this service activity are that the use of RENGSE equipment in Mekar Jaya Village shows good technical performance, with an average combustion capacity of 95-100 kg/hour and an operational time of around 8 hours/day. For 30 days, this tool is able to process about 24 tons of waste. From the social side, there has been a significant change in people's behavior patterns, where households that sort waste have increased from 10% to 68%. Conclusion: RENGSE utilization activities have succeeded in increasing the effectiveness of waste management in Mekar Jaya Village technically and socially with 87% positive responses. The application of this technology can be said to be efficient in reducing the volume of waste because it is able to reduce up to 70% of waste to landfills, as well as encourage changes in community behavior towards more responsible, independent, and sustainable waste management.